First person – Krittika Sudhakar (Biology Open, 2022)
First Person is a series of interviews with the first authors of a selection of papers published in Biology Open, helping early-career researchers promote themselves alongside their papers. Krittika Sudhakar is first author on ‘Alterations in lifespan and sleep:wake duration under selective monochromes of visible light in Drosophila melanogaster’, published in BiO. Krittika conducted the research described in this article while a PhD student (DST-INSPIRE-senior research fellow) in Dr. Pankaj Yadav's lab at SASTRA University, Tirumalaisamudram, India. She is now a Postdoctoral Fellow in the lab of Dr. Adelheid Lempradl at the Van Andel Institute, Michigan, USA, investigating Deciphering the short and long-term effects of nutrition influences Drosophila physiology, aging and metabolism.